Water Absorption and Erosion Resistance Properties of Soil Blocks Stabilised with Cissus Populnea Stem Fibre-Infused Water (International Journal of Engineering Materials and Manufacture, 2025)
The imminent shortage of conventional building materials coupled with environmental concerns due to the manufacturing processes underscore the need for innovative and sustainable solutions. In soil material improvement, research is being shifted into the use of agricultural-based materials for soil stabilisation. It is against this background that, this study investigated the water absorption and erosion resistance of soil blocks stabilised with Cissus populnea fibre-infused water. To determine the effect of the Cissus populnea fibre-infused content on the soil blocks water absorption and erosion resistance, the infusion concentrations in the mixing water was varied from 0%, 7.5%, 10%, 12.5% and 15% by weight of the water. A total of 75 blocks were produced and tested at 28 days. From the results, the control blocks absorbed 0.47% water while blocks stabilised with 15% Cissus populnea fibre-infused water absorbed 0.23% water, representing 51% reduction in the block water absorption. Furthermore, erosion decreased from 5.5mm, 4.5mm, 2.6mm, 0.0mm and 0.0mm for the 0%, 7.5%, 10%, 12.5% and 15% Cissus populnea fibre infusion respectively. The study therefore concludes that Cissus populnea fibre-infused water, particularly at 12.5% and 15% infusions, positively enhanced the durability of soil blocks, making them suitable for soil housing applications.